The Armenian Diaspora in Rio de Janeiro: Micro-Histories of Identity, Memory and Solidarity during the Armenian Genocide - Júlia de Moraes Cabral Tordeur (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
This article examines the role of Mihran Latif, an Armenian immigrant and a key figure among the elite of Rio de Janeiro, in supporting survivors of the Armenian Genocide and promoting the Armenian cause in Brazil. Using a micro-historical approach, the study explores Latif’s personal trajectory within the broader context of the Armenian diaspora in Rio, a community often overshadowed by the larger Armenian presence in São Paulo. The research draws on primary sources, including immigration dossiers, naturalization records from the Brazilian National Archive’s SIAN system, and periodicals. These sources provide insights into the solidarity networks Latif helped establish, illustrating how local elites mobilized resources to support genocide survivors and preserve cultural identity. By focusing on Latif’s initiatives and those of other key figures, the article sheds light on the mechanisms of community building, the intersection of citizenship and diasporic identity, and the significance of elite involvement in post- genocide solidarity efforts. This analysis contributes to the historiography of the Armenian diaspora in Brazil, offering a fresh perspective on the role of elites in shaping collective memory and identity. The article challenges the dominant focus on the São Paulo community, emphasizing the importance of individual narratives in understanding the broader dynamics of the diaspora.
Keywords: Armenian genocide